2018
DOI: 10.1016/j.amjms.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Low Pharmacy Refill Adherence Among Older Hypertensive Men and Women by Race

Abstract: Background: Sex-race stratification may lead to identification of risk factors for low antihypertensive medication adherence that are not apparent when assessing risk factors in women and men without race stratification. We examined risk factors associated with low pharmacy refill adherence across sex-race subgroups (white women, black women, white men, black men) within the Cohort Study of Medication Adherence among Older Adults (n=2,122). Methods: Pharmacy refill adherence was calculated as proportion of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Another predictor of adherence found in the present study was patients’ annual income, as patients with higher annual income were more likely to be adherent to antihypertensive drugs. Several studies have also come to similar results (Lemstra and Alsabbagh, 2014; Ma, 2016; Williams et al, 2018), and patients with lower income tend to have reduced antihypertensive drug use due to costs.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Another predictor of adherence found in the present study was patients’ annual income, as patients with higher annual income were more likely to be adherent to antihypertensive drugs. Several studies have also come to similar results (Lemstra and Alsabbagh, 2014; Ma, 2016; Williams et al, 2018), and patients with lower income tend to have reduced antihypertensive drug use due to costs.…”
Section: Discussionmentioning
confidence: 72%
“…Several factors associated with poor or non-adherence have also been identified in many recent studies. These include socio-demographic factors (Abegaz et al, 2017; Nurhussein et al, 2018; Fatani et al, 2019; Uchmanowicz et al, 2019), such as gender, age, education level, occupational status, or even race; socio-economic status, such as annual income and medical insurance (Boima et al, 2015; Nielsen et al, 2017); and family disease history, number of prescribed drugs, comorbidity, and duration of hypertension as clinical disease-related factors (Choi et al, 2018; Williams et al, 2018; Uchmanowicz et al, 2019). Furthermore, psychosocial factors also influence medication adherence, such as depressed emotion, perceived severity of disease, self-rated health, perceived symptoms, and self-efficacy (Al-Noumani et al, 2018; Asgari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…n = 400 in the fully adjusted model testing the association between low K-Wood-MAS-4 adherence and decline in PCS). Race differences in adherence [ 36 ] and HRQOL [ 37 ] warrant further research with larger subgroup samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, including uncontrolled BP and healthy lifestyle modifications in regression models did not substantially change the association between low adherence and decline in HRQOL. Moreover, controlling for comorbidities, which are associated with both low adherence [ 36 ] and low HRQOL [ 44 ], did not attenuate the relationship between low adherence and decline in HRQOL. Finally, including number of classes of antihypertensive medications in the models as a measure of medication burden did not change the association between low adherence and decline in HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…40 Control of illness was the most significant predictor of a favorable outcome 41 Patients who believed in their own ability to control illness and had strong confidence in management plan reported better medication adherence in many studies. 10,16,42 Hsiao and colleagues 43 reported that there is a negative association between patients' beliefs about their control of illnesses, emotional representation and medication adherence. Illness perceptions are influenced by information that patients receive from health care professionals and the satisfaction with the information received.…”
Section: Educationmentioning
confidence: 99%